Some New Perspectives on Global Domination in Graphs. (20th August 2013) - Vaidya, S. K.; Pandit, R. M.
Abstract : A dominating set is called a global dominating set if it is a dominating set of a graph G and its complement G ¯ . Here we explore the possibility to relate the domination number of graph G and the global domination number of the larger graph obtained from G by means of various graph operations. In this paper we consider the following problem: Does the global domination number remain invariant under any graph operations? We present an affirmative answer to this problem and establish several results.